The Influence of Job Satisfaction on Turnover Intention (Survey on Contract Employees of Administrative Staff at Maranatha Christian University) - Sitohang, Helen Namora; Munthe, Rusli Ginting (Lentera Ilmu Nusantara, 2024)
This research was designed to evaluate the impact of job satisfaction on turnover intention among contract administrative staff at Maranatha Christian University, Bandung. A quantitative approach was employed, involving all 39 contract employees as a sample through census sampling. Data were gathered using a Likert-scale questionnaire and analyzed through validity tests (Pearson correlation), reliability, normality, and simple linear regression. The findings reveal that job satisfaction does not significantly influence turnover intention , with a significance value (Sig) of 0.182, exceeding the threshold of 0.05. This result suggests that job insecurity due to contract status plays a more significant role in driving turnover intention than job satisfaction. The study recommends that the university prioritize job stability and career development opportunities to reduce turnover intention among contract employees.